Pengaruh Tingkat Pendidikan dan Kesehatan terhadap Produktivitas Tenaga Kerja di Provinsi Aceh. - Adnan, Muhammad; Marwiyati; Jannah, Riadhil (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Employment is a fundamental thing in human life because it includes social and economic dimensions. Providing sufficient job opportunities is one of the important goals in economic development in order to catch up with the labor force, because the growth of the labor force is faster than the growth of employment opportunities. The problem of job opportunities is an important thing in the macro economy and labor is one of the factors of production besides technology and capital. Efforts to encourage increased productivity of human labor are through education and health. This study aims to determine how much influence the level of education and health has on labor productivity. This research is a quantitative study using secondary data in the form of panel data, the data obtained from BPS Aceh. The method used is a less square panel with a random effect model. The results of this study indicate that the education level variable has a positive and significant effect on labor productivity in Aceh Province in 2010-2020, while health has a negative and insignificant effect on labor productivity in Aceh Province in 2010-2020. Simultaneously the level of education and health does not have a significant effect on labor productivity.